Pengetahuan Orang Tua Tentang Stimulasi Deteksi Intervensi Dini Tumbuh Kembang Anak di Wilayah Kerja Puskesmas Sangkali Kota Tasikmalaya - Winda Windiyani; Sri Wahyuni Sundari; Melsa Sagita Imaniar (Jurnal Medika Cendikia, 2020)
Knowledge and understanding of the growing toddler and the development of early growth and progression in order to see whether the child is experiencing disruption or delay in its development should have been possessed by the parents since the early age (Sujono Riyadi & sukarmin, 2009: Sudirmanm 2016). The study aims to determine the extent to which parents ' knowledge of early intervention detection is growing children. The type of research used is descriptive, the population of all parents who have children from the age of 0-72 months who come to the Posyandu, samples of 44 elderly, sampling techniques using accidental sampling, research instruments using questionnaires. Data analysis using UNIVARIAT analysis. More than 50% of parents have good knowledge. Advice is expected that all parents can know the growth and development of children so that it can prevent the occurrence of growth delay and development of children.